Ảnh hưởng của cấu trúc chất mang tới khả năng làm việc của xúc tác CO/SiO2 trong quá trình tổng hợp Fischer-Tropsch - Thanh Hà, Đỗ Thị; Liên, Nguyễn Hồng; Huyền, Phạm Thanh (Vietnam Journal of Chemistry, 2014)
The influence of the support texture (Silicagel, Silicalit and MCM-41) on working performance of Co/SiO2 for the Fischer-Tropsch synthesis has been studied. The differences in textures of three SiO2 types were characterized by BET, SEM and FE-SEM-EDX techniques. The results showed that different textures of the three SiO2 materials strongly affected not only on distribution of catalytic sites (cobalt) over the support but also on catalytic activity and selectivity. Keywords: Liquid fuel, syngas, Fischer-Tropsch, Co/SiO2 catalyst.